FINANCIAL ANALYSIS OF BROILER CHICKEN FARMING BUSINESSES WITH TURMERIC AND DRAGON FRUIT EXTRACT IN DRINKING WATER - D., Surya; Suarta, G.; Sukanata, I W. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
This study aims to determine the farm income of Broiler Chickens given turmeric extract (Curcuma domestica) and dragon fruit peel extract (Hylocereus polyrhizus). This study was conducted for twenty-eight days in the chicken coop of Dr. Ir. Gede suarta M.Si, Mengwi, Bali. The design used w|as |a completely r|andomized design (CRD) consisting of 4 tre|atments |and 4 replic|ates with |a tot|al of 80 broilers used. The tre|atment given is drinking w|ater without turmeric extr|act |and dr|agon fruit peel extr|act which is used |as |a control (P0), drinking w|ater given 4% turmeric extr|act (P1), drinking w|ater given 4% dr|agon fruit peel extr|act (P2), drinking w|ater given 2% turmeric extr|act |and 2% dr|agon fruit peel extr|act (P3). The observed v|ari|ables include income |an|alysis b|ased on cost, revenue, income, R/C r|atio |and BEP. The results showed th|at Broiler Chickens without the provision of turmeric extr|act |and dr|agon fruit peel extr|act |as much |as g|ave the best results with |an income of Rp438,111.00, - / period with |an R / C r|atio value of 1.569. BEP production unit as much as 19.37 kg of Broiler chicken carcass, BEP selling price of Broiler chicken per kg Rp21,982.-/kg whole carcass weight, BEP revenue of Rp769,398,-/per period. Based on the results of the study, it can be concluded that Broiler farming without the provision of turmeric extract and dragon fruit peel extract can have the highest level of efficiency